2008
DOI: 10.1111/j.1749-6632.2008.03452.x
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Understanding of the Genetic Etiology of Vertebral Segmentation Disorders in Humans

Abstract: Vertebral malformations contribute substantially to the pathophysiology of kyphosis and scoliosis, common health problems associated with back and neck pain, disability, cosmetic disfigurement, and functional distress. This review explores (1) recent advances in the understanding of the molecular embryology underlying vertebral development and relevance to elucidation of etiologies of several known human vertebral malformation syndromes; (2) outcomes of molecular studies elucidating genetic contributions to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 144 publications
(288 reference statements)
2
81
1
Order By: Relevance
“…In contrast to children with adolescent idiopathic scoliosis, children with EOS represent a heterogeneous population. Children may have infantile idiopathic scoliosis with no other associated comorbidities or may have a primary thoracic insufficiency with severe pulmonary problems, as is present, for example, in Jarcho-Levin syndrome [24,25]. In order to understand the child with a crooked spine, we need a basis for differentiating the many different groups inherent in this population.…”
Section: Does the Deformed Spine Grow Like The Normal One? Alain Dimementioning
confidence: 99%
“…In contrast to children with adolescent idiopathic scoliosis, children with EOS represent a heterogeneous population. Children may have infantile idiopathic scoliosis with no other associated comorbidities or may have a primary thoracic insufficiency with severe pulmonary problems, as is present, for example, in Jarcho-Levin syndrome [24,25]. In order to understand the child with a crooked spine, we need a basis for differentiating the many different groups inherent in this population.…”
Section: Does the Deformed Spine Grow Like The Normal One? Alain Dimementioning
confidence: 99%
“…The HVF mouse model resembles the failure of segmentation (block vertebrae) pattern (Figs. 1 and 2; Table 1) which has been reported in ∼3% of 251 patients with congenital scoliosis,44 and to have a prevalence of approximately 0.5 to 1 per 1000 individuals 9. Thus, identifying the genetic defect causing HVF may help to identify a component in the complex pathways regulating vertebral formation, which is likely to involve the expression of multiple genes.…”
Section: Discussionmentioning
confidence: 99%
“…Kyphosis, scoliosis, or kyphoscoliosis, can occur at any age, secondary to other underlying developmental, musculoskeletal, neuromuscular, or spinal disorders,5, 6, 7, 8, 9, 10 and may be part of complex disorders such as the CHARGE syndrome (coloboma of the eye, heart defects, atresia of the nasal choanae, retardation of growth and/or development, genital and/or urinary abnormalities, and ear abnormalities and deafness),9, 11 or occur as a nonsyndromic condition. Indeed, the most common forms of kyphosis and scoliosis in adolescents are nonsyndromic and include: Scheuermann disease3 a form of nonsyndromic kyphosis, which affects >8% of the population12; idiopathic scoliosis (IS), which affects approximately 2% to 3% individuals13, 14, 15, 16; and congenital nonsyndromic scoliosis, which is reported to have a prevalence of approximately 0.5 to 1 per 1000 individuals 9. Familial and twin studies have indicated a genetic basis for kyphosis17, 18, 19, 20 and scoliosis,21, 22, 23, 24, 25, 26, 27, 28 with likely genetic heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sclerotome cell divides in a cranial and a caudal part. The spinal nerves leave the neuronal tube and migrate to the sclerotome center where they innervate the myotomes [1]. …”
Section: Discussionmentioning
confidence: 99%